Bodily constraints contributing to multimodal referentiality in humans: The contribution of a de-pigmented sclera to proto-declaratives. (May 2017) - Perea García, Juan Olvido; Ehlers, Katrine Rosendal; Tylén, Kristian
Abstract: We present the results of an empirical study that measured the contribution of a conspicuous eye-gaze (as a function of scleral de-pigmentation) of humans in conveying multimodal referentiality by combining visual and auditory cues in a naturalistic setting. We made participants interact in a cooperative task in which they had to convey referential meaning about co-presential entities. In one of the conditions, participants had no access to their interactants' eye-gaze. We interpret the results as supporting the idea that our eye morphology contributes to instantiating multimodal referentiality in cooperative tasks in peripersonal space. Highlights: Eye-gaze significantly contributes to multimodal referentiality in cooperative tasks. Disrupting it decreases performance of tasks that require coordination of attention. A de-pigmented sclera might have been a prerequisite in establishing common ground. Multimodal referentiality underlied vocal intentional communication in our ancestors.